Toward community standards in the quest for orthologs - Dessimoz, C.; Gabaldon, T.; Roos, D.S.; Sonnhammer, E.; Herrero, J.; Quest for Ortholog Consortium (Oxford University Press, 2012)
The identification of orthologs—genes pairs descended from a common ancestor through speciation, rather than duplication—has emerged as an essential component of many bioinformatics applications, ranging from the annotation of new genomes to experimental target prioritization. Yet, the development and application of orthology inference methods is hampered by the lack of consensus on source proteomes, file formats and benchmarks. The second ‘Quest for Orthologs’ meeting brought together stakeholders from various communities to address these challenges. We report on achievements and outcomes of this meeting, focusing on topics of particular relevance to the research community at large. The Quest for Orthologs consortium is an open community that welcomes contributions from all researchers interested in orthology research and applications.Contact: dessimoz@ebi.ac.uk